Analisis Konstruksi Jembatan Busur Rangka Baja Tipe A-half Through Arch - Bayzoni Bayzoni; Eddy Purwanto; Yumna Cici Olyvia (UNIVERSITAS LAMPUNG, 2015)
Indonesia is an archipelago and has an important role connecting bridges between islands . The need for long -span bridges and lightweight materials and consist artistic value , then the arc steel truss bridge is an alternative of the problem. In this research will focus on the type a half through arc.The bridge is design to 120 m,span and 12 m,height with a transverse dimension of the vehi- cle floor complete with sidewalk is 11 m to 2 lanes 2 -way with pavement width of 1 m . Loading calculations used in the planning of the bridge is based on the regulation BMS 1992 and RSNI T - 02-2005 and calculation of the power structure refers to RSNI T - 03-2005 and SNI 03-1729-2002. The results of the study are obtained composite vehicle floor plates , with a reinforced concrete slab thickness of 250 mm . Transverse girder and longitudinal girder using iwf.900.300.28.16 iwf.400.200.13.8 with BJ 55. The connection between the ransverse girder and longitudinal girder using bolts with A325 quality with a diameter of 25 mm with 10 mm thick plate BJ 34. The main structure of the arc in the form iwf.400.400 .21.13 . The main structure connection using bolts with A325 quality with a diameter of 35 mm with 25 mm thick plate BJ 50 .